The performance of asphalt-concrete wearing-course (AC-WC) mixture by using rice husk ash as filler with the addition of asbuton in asphalt pen 60/70 as binder - Maizal Kamil; Renni Anggraini; Fitrika Mita Suryani (Syiah Kuala University, 2011)
The supply of stone dust as filler and asphalt as binder is limited, therefore it is necessary to use an alternative to filler and asphalt import. The problem is expected to be overcome by the presence of rice husk ash as a filler and natural asphalt of Buton Island (Asbuton) as a binder. This study aims to evaluate the performance of Asphalt Concrete-Wearing Course (AC-WC) mixture by using rice husk ash as a filler and asphalt penetration 60/70 as binder with the addition of Asbuton. The specimens were made into two major groups: (i) the specimens using stone dust and asphalt pen 60/70 (ABA), and (ii) the specimens using rice husk ash and asphalt pen 60/70 with the addition of asbuton (ASA). The last group was performed with four variations: 0% (ASA 0), 5% (ASA 5), 10% (ASA 10), and 15% (ASA 15) over the total weight of the mixture. Total specimens were 75, each has 15 specimens. Asphalt contents used were 4.5% to 6.5%. Specifications used the standards of the Departemen Permukiman dan Prasarana Wilayah (2005) by using Marshall method Optimum asphalt contents (OAC) for each mixture were 5.6% (ABA), 6.0% (ASA 0), 6.3% (ASA 5), 5.9% (ASA 10), and 5.8% (ASA 15). In sum, the asphalt concrete mixture using rice husk ash as filler was able to compete with the one using stone dust as filler, and therefore can be used as alternative materials to road pavement construction.